2018
DOI: 10.1021/acs.langmuir.8b01234
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Conductivity Strongly Influences Bump and Crater Formation on Electrodes during Charge Transfer

Abstract: Aqueous droplets acquire charge when they contact electrodes in high voltage electric fields, but the exact mechanism of charge transfer is not understood. Recent work by Elton et al. revealed that electrodes are physically pitted during charge transfer with aqueous droplets. The pits are believed to result when a dielectric breakdown arc occurs as a droplet approaches the electrode and the associated high current density transiently locally melts the electrode, leaving distinct crater-like deformations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…The experimental setup (Figure , top) is similar to those used in previous experiments. ,, Standard photolithography techniques were used to deposit gold electrodes 1 mm wide, 20 mm long, and 50 nm thick onto glass substrates. For each experiment, two new electrodes were placed in a plastic cuvette and separated by nonconducting spacers at the top and bottom.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup (Figure , top) is similar to those used in previous experiments. ,, Standard photolithography techniques were used to deposit gold electrodes 1 mm wide, 20 mm long, and 50 nm thick onto glass substrates. For each experiment, two new electrodes were placed in a plastic cuvette and separated by nonconducting spacers at the top and bottom.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A limiting prediction for the amount of charge a droplet should acquire upon contact with an electrode was derived by James Maxwell, who showed that the amount of charge Q a perfectly conducting sphere would acquire from a perfectly conducting planar electrode is given by Here, a is the sphere radius, εε o is the permittivity of the surrounding liquid, and E is the applied electric field. Although the amount of charge the liquid droplets acquire generally follows this dependence on electric field strength and droplet radius, for unclear reasons droplets have not been observed to acquire as much charge as predicted by Maxwell. ,, Solid particles have also been observed to obtain less than the predicted amount of charge, again for unclear reasons. ,, …”
Section: Introductionmentioning
confidence: 93%
“…The studies in the microfluidics field started from 2006 in microchannels and from 2009 in a digital microfluidic system . Since 2010, active research on various topics has been reported in industrial and biological applications and in microfluidics technology. Basic research on the CCEP phenomenon also has been actively studied by various groups on droplet dynamics, electrohydrodynamics, , interfacial phenomena, , and basic principles and charge measurement. Recent progress in ECD based digital microfluidic technology is noticeable, and the application to electroporation showed promising results. These diverse studies of CCEP have improved the underlying understanding even further, suggesting and verifying the potential features of microfluidic technology.…”
Section: Introductionmentioning
confidence: 99%
“…where is kinematic viscosity [23,24]. There are five parts in the equation 8 including variation ( ), conviction (( ) ), diffusion ( ), internal source ( ) and external source ( ) respectively.…”
Section: The Momentum Equation Can Be Written Asmentioning
confidence: 99%